A study of agronomical practices for cultivation of selected plants for better yield - ALOK KUMAR (International Journal of Multidisciplinary Research and Studies, 2020)
Recent gains in crop yield may be primarily attributed to many factors, the most important of which are advancements in breeding and agronomy, as well as modifications to the spatial and temporal organization of crop production within agricultural systems. It is a widely held belief that one of the key variables that leads to higher productivity is the interaction that takes place between breeding and agronomy. For instance, dwarfing genes in cereals resulted to a physiological improvement in the grain/stem partitioning of dry matter, which had direct ramifications for yield. This improvement allowed for a greater proportion of grain to stem dry matter. When compared to previous, taller cultivars, these genes made it possible to apply larger rates of nitrogen fertilizer while simultaneously minimizing the danger of lodging. This was made possible by the combination of the two factors. It is vital to highlight that grass herbicides were necessary in order to take advantage of the benefits afforded by short-stature grains in automated production systems. This is something that should not be overlooked.